2013
DOI: 10.1155/2013/301875
|View full text |Cite
|
Sign up to set email alerts
|

Computational Approaches for Modeling the Multiphysics in Pultrusion Process

Abstract: Pultrusion is a continuous manufacturing process used to produce high strength composite profiles with constant cross section. The mutual interactions between heat transfer, resin flow and cure reaction, variation in the material properties, and stress/distortion evolutions strongly affect the process dynamics together with the mechanical properties and the geometrical precision of the final product. In the present work, pultrusion process simulations are performed for a unidirectional (UD) graphite/epoxy comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…The following modifi ed Darcy model is solved in the porous region: [5.44] where U represents the velocity vector of the porous medium. It should be noted that the component of the velocity vector U aligned with the pull direction is constant, and it is the only non-zero term in the straight portions of the domain, while other components need to be locally modifi ed by considering the geometric confi guration of the tapered zone [75,84]. The FVM, as implemented in the commercial package ANSYS-CFX, was used here to solve the impregnation model, particularized to the case study reported in [76], simulating the pultrusion process of a unidirectional graphite/epoxy composite rod with a circular cross-section whose radius was 4.75 mm.…”
Section: Impregnation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The following modifi ed Darcy model is solved in the porous region: [5.44] where U represents the velocity vector of the porous medium. It should be noted that the component of the velocity vector U aligned with the pull direction is constant, and it is the only non-zero term in the straight portions of the domain, while other components need to be locally modifi ed by considering the geometric confi guration of the tapered zone [75,84]. The FVM, as implemented in the commercial package ANSYS-CFX, was used here to solve the impregnation model, particularized to the case study reported in [76], simulating the pultrusion process of a unidirectional graphite/epoxy composite rod with a circular cross-section whose radius was 4.75 mm.…”
Section: Impregnation Analysismentioning
confidence: 99%
“…Numerical and experimental investigations of different aspects of the pultrusion process have been reported in the literature, focusing mainly on issues related to heat transfer and curing [63,[65][66][67][68][69][70][71][72][73][74], the pressure distribution [75,76] and the pulling force [77][78][79][80][81][82][83]. However, the proposed models often neglect the interactions between some of the phenomena involved, graphically schematized in Figure 5.19 , on the Multi-physics involved in the pultrusion process and related interactions [84] basis of some simplifying assumptions. In what follows, some numerical models dealing with the analysis of impregnation, thermochemical aspects and the pull force are reported.…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of using pulltrusion have been reported in detail in [1]. Numerical modeling studies of the pulltrusion process have been carried out in connection with the DeepWind [5][6][7][8][9][10][11][12].…”
Section: Rotor Bladesmentioning
confidence: 99%
“…In recent years, the pultrusion process experienced a remarkable growth within the composite industry, due to its cost-effectiveness, automation, and high quality of products. Nowadays, the process is widely used to manufacture wind turbine blades, window profiles, door panels, and reinforcing bars for concrete [2,3]. A lot of numerical simulations have been done in the last twenty years because a practical set up of pultrusion process is not possible without a numerical analysis of the technological process [4].…”
Section: Introductionmentioning
confidence: 99%